Differential Induction of Long-Term Potentiation in the Horizontal versus Columnar Superficial Connections to Layer II Cells of the Entorhinal Cortex - Li Ma; Angel Alonso; Clayton T. Dickson (Neural Plasticity)
The entorhinal cortex (EC) is a nodal and independent mnemonic element of the medial temporal lobe memory circuit as it forms a bidirectional interface between the neocortex and hippocampus. Within the EC, intra- and inter-lamellar associational connections occur via horizontal and columnar projections, respectively. We undertook a comparative study of these two inputs as they converge upon EC layer II cells using whole-cell patch techniques in an adult rat EC horizontal slice preparation in which the deepest layers (V-VI) had been dissected out. Electrical stimulation of layers I and III during GABA blockade allowed us to study excitatory synaptic properties and plasticity in the horizontal and columnar fibre systems, respectively. Both pathways exhibited AMPA- and NMDA-receptor mediated transmission and both exhibited long-term potentiation (LTP) after high-frequency (tetanic) stimulation. LTP in the horizontal, but not in the columnar pathway, was blocked by NMDA receptor antagonism. Intriguingly, LTP in both appeared to be mediated by post synaptic increases in Ca2+ that may be coupled to differing second messenger pathways. Thus, the superficial excitatory horizontal and columnar associative pathways to layer II have divergent mechanisms for LTP which may endow the EC with even more complex and dynamic processing characteristics than previously thought.